The English Language in India: From Racial-Colonial to Democratic (European Journal of Behavioral Sciences, 2020)
In India and the other countries of the global south, a non-native variety of English Language has been serving the interest of the socio-cultural needs. Such a variety suits to the interest of the young learners since they have already mastered the tools of communication from outside the class room. Even the seasoned writers and columnists have developed a tendency to experiment further and develop suitable material for language teaching which was previously dependent on prescriptive grammar and lexical structures. This calls for an investigation into the nature of a shift within the very core of this language in India. This Paper tries to draw a graph on the course of this shift by examining data collected from mass media and situate this fresh use of language at a democratic space unlike the monolith of language as practiced in past. The news entries are trendy and user friendly, contain morphological and syntactic novelty that provides suitable methods to support pedagogy. It is fascinating to see how such data holds a promise of huge curricular implications providing a pragmatic road map for the teaching of theory, literature, and English language in India rather than development of mere skills as done in past.